Do Higher Education Institutions Foster Critical Thinking? – Students' Perspective - Mirela Mabić; Dražena Gašpar (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Rovinj, Croatia, 12-14 September 2019, 2019)
The paper presents the results of research related to students' perception of enhancing their critical thinking during studies at higher education institutions (HEIs). The authors developed a questionnaire and conducted the research at the public universities in Bosnia and Herzegovina (BH) in order to investigate students' perception of enhancing their critical thinking during studies at the university. Namely, in a 21st century, the employability of fresh graduates highly depends on their soft skills, especially their ability to think critically in solving the problems. The aim of the presented research is to find if BH students are aware of the necessity to enhance their critical thinking abilities during their studies in order to be better prepared for their future jobs.
Keywords: I23; J24; 330; critical thinking; higher education institutions; students